Climatology of waterspouts in Mexico and numerical modeling of a particular case - Daniela Monterde; Noel Carbajal; José Francisco León-Cruz; Luis Felipe Pineda-Martínez (Environmental Research Communications)
Numerous waterspout events occur practically in all Mexican waters. The principal aim was to carry out a climatology of these events. A data compilation allowed the identification of 103 cases from 2010–2022. A Szilagyi waterspout nomogram was constructed to explain the formation mechanism using the ERA5 reanalysis data. The nomogram classified waterspout events according to their origin using thermodynamic parameters. The results revealed that the thermodynamics of some waterspouts in Mexico do not fit the current definition of the Szilagyi nomogram. Most waterspouts are thunderstorm-related and fit the nomogram. A minority that arises from land breezes and upper-low conditions also fit. A relevant case, which occurred in an area with a recurrent incidence of waterspouts, allowed observation of relevant dynamic properties, such as its strength, occurred on August 8, 2019, in Coatzacoalcos, Veracruz. The documented waterspout trajectory revealed that it moved through the sea and city. The Weather Research and Forecasting (WRF) model was used for modeling this event at a resolution of 250 m. The results showed the instability, a cyclonic disturbance (misocyclone) that caused the waterspout. The analysis showed the behavior of meteorological variables, such as temperature, humidity, wind, vorticity, and unstable atmospheric variables during the storm.